1988
DOI: 10.3354/meps045271
|View full text |Cite
|
Sign up to set email alerts
|

Use of 13N as tracer for bacterial and algal uptake of ammonium from sea-water

Abstract: The relative importance of phytoplankton and heterotrophlc bacteria in the ut~lization of ammonium in a temperate coastal pelaglc environment (Long Island Sound. New York, USA) was examined uslng the short-lived radioisotope, I3N Uptake of ' 3~~: Into different slze fractions under simulated in situ temperature and light condihons was compared to size fractionations of bacterial abundance, chlorophyll, and uptake of tritlated thymidme and 14C-b~carbonate In January and Apnl, little ' 3~ entered the bactenal sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 16 publications
(21 reference statements)
3
38
0
1
Order By: Relevance
“…If bacteria in the Sargasso Sea were growing on C : N substrates > 10: 1 then they may not have been significant regenerators of inorganic nitrogen. Thls is consistent with observations from several marine systems showing that bacteria take up ammonium (Wheeler & Kirchman 1986, Fuhrman et al 1988, Suttle et al 1990, and provides further evidence that much of the regeneration of inorganic nitrogen results from consumption of phytoplankton and bacteria by predators (e.g. Sherr et al 1983, Goldman et al 1985.…”
Section: Respiration and Turnoversupporting
confidence: 74%
“…If bacteria in the Sargasso Sea were growing on C : N substrates > 10: 1 then they may not have been significant regenerators of inorganic nitrogen. Thls is consistent with observations from several marine systems showing that bacteria take up ammonium (Wheeler & Kirchman 1986, Fuhrman et al 1988, Suttle et al 1990, and provides further evidence that much of the regeneration of inorganic nitrogen results from consumption of phytoplankton and bacteria by predators (e.g. Sherr et al 1983, Goldman et al 1985.…”
Section: Respiration and Turnoversupporting
confidence: 74%
“…Incubations were carried out under simulated in situ conditions of light and temperature in l-liter polycarbonate flasks. As in other studies with i3NH,+ in seawater (Fuhrman et al 1988), we found that Formalin-killed controls did not adsorb appreciable isotope-presumably because of the many competing cations in seawater. At closely spaced time intervals, 15-ml subsamples were filtered through 0.2-, l.O-, and 3.0-pm polycarbonate filters (Nuclepore).…”
supporting
confidence: 65%
“…2C). Other observations have shown that this uptake is attributable to bacteria (Fuhrman et al 1988). The partitioning of this flux into different size classes was very sensitive to small changes in NH,' concentration.…”
mentioning
confidence: 88%
“…Billen & Fontigny (1987) consistently observed DFAA uptake rates that exceeded N-demand by as much as 600 % . Fuhrman et al (1988) and Fuhrman (1990) also observed DFAA uptake that occasionally exceeded N-demand. Our approach was quite different from that of these previous investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially important nitrogen source for bacteria is ammonium. Bacteria can account for a substantial fraction (ca 50 %) of total NHZ uptake in seawater (Wheeler & Kirchman 1986, Fuhrman et al 1988, Kirchman et al 1989. Tupas & Koike (1990) showed that NH; could support as much as 50 to 88 % of bacterial N-demand, even when large amounts of dissolved organic nitrogen (DON) were utilized.…”
Section: Introductionmentioning
confidence: 99%